Interplay between survival and regulated cell death mechanisms during periodontitis progression: a systematic review - Alfredo Torres; Leonardo Díaz; Jaime Oyarzún; M. Angélica Michea; Xiaowei Xu; Flavio Salazar-Onfray; Fermín E. González (Japanese Dental Science Review)
Regulated cell death (RCD) and survival pathways have emerged as critical factors in periodontal tissue breakdown. However, their precise roles and interactions remain poorly understood. This systematic review aimed to synthesize current evidence regarding the involvement of RCD and survival mechanisms in the progression of periodontitis. A systematic literature search was conducted in PubMed/MEDLINE, Web of Science and Scopus, complemented by manual searching in Google Scholar, following PRISMA guidelines. After removing duplicates, 549 studies underwent title and abstract screening. Of these, 56 articles were selected for full-text review and 18 studies met the eligibility criteria and were included in the final synthesis. Ferroptosis, pyroptosis and necroptosis were consistently associated with inflammatory exacerbation, alveolar bone loss and disease progression. In contrast, autophagy and apoptosis exhibited dual roles—protective or destructive—depending on cell types, disease stage and experimental conditions. Most studies utilized ligature-induced periodontitis animal models. Several studies also demonstrated the therapeutic potential of modulating specific RCD pathways to control inflammation and promote periodontal tissue regeneration, highlighting possible translational strategies for host-modulation therapy of periodontitis. This systematic review consolidates the pivotal role of RCD in the progression of periodontitis. Targeting RCD pathways may represent novel therapeutic strategies to reduce periodontal inflammation and tissue destruction.